2021
DOI: 10.18280/jesa.540207
|View full text |Cite
|
Sign up to set email alerts
|

Development of Machine Vision to Increase the Level of Automation in Indonesia Electronic Component Industry

Abstract: Human involvement in the assembly part manufacturing process is still relatively high. However, automation solutions are not flexible enough to be applied to manufacturing systems. It is essential to evaluate each work activity so that automation can be implemented effectively. We developed an automatic vision inspection using machine vision. The level of automation (LoA) in the company increases, and the impact caused by process failures on manual systems can be eliminated during inspection activities. The au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This research uses a methodology to run in a systematic and directed manner. The steps that design improvements use the Dynamo++ steps [28,30]. The stages used include Pre-study, measurement, analysis, and implementation, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This research uses a methodology to run in a systematic and directed manner. The steps that design improvements use the Dynamo++ steps [28,30]. The stages used include Pre-study, measurement, analysis, and implementation, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The stages used include Pre-study, measurement, analysis, and implementation, as shown in Fig. 1 for dynamo++ stages [28,30].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By combining cablebased parallel robots and machine vision, it is used as a proposal for detecting rusty bolts and liner plate edge leaks in the coal bunker maintenance process [12]. With inexpensive equipment and without human intervention, the detection of color and dent defects on sandwich panel parts can be well detected by automatic visual inspection [13]. At the electronics company, machine vision was developed to increase automation and speed up the change-over product process [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, companies must continue to pay attention to the delivery time limit, costs to be incurred, and the quality of their products so that they are in line with market demand [6]. Quality management methods are successfully used in business process development and need to be continuously improved in terms of adapting business models so that companies become more competitive [7].…”
Section: Introductionmentioning
confidence: 99%